1988
DOI: 10.1159/000111955
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine Synthetase: A Marker of an Astroglial Subpopulation in Primary Cultures of Defined Brain Areas

Abstract: Primary cultures from various areas of newborn mouse brain were developed and characterized. Enriched astroglial cultures of the cerebral hemispheres, cerebellum, medulla oblongata and olfactory bulbs contained about 80–90% glial fibrillary acidic protein (GFA) immunolabelled cells. These cultures were composed of a majority of flat, ''protoplasmic-like'' cells. The aim of this culture model was used: (1) to study glutamine synthetase (GS) activity during in vitro astroglial development; (2) to consider the hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Glutamine synthetase (Fig. 2D), an enzyme that converts glutamate to glutamine was expressed in some but not all horizontal astrocytes (Fages et al, 1988; (Seri et al, 2001). D cells have a very different ultrastructure to that of both types of astrocytes described above.…”
Section: Cell Types Of the Sgzmentioning
confidence: 84%
“…Glutamine synthetase (Fig. 2D), an enzyme that converts glutamate to glutamine was expressed in some but not all horizontal astrocytes (Fages et al, 1988; (Seri et al, 2001). D cells have a very different ultrastructure to that of both types of astrocytes described above.…”
Section: Cell Types Of the Sgzmentioning
confidence: 84%
“…This ABHD6 staining may in fact be glial in nature. To test this, we costained with glutamine synthetase, a marker for some astrocytes and oligodendrocytes (Norenberg and Martinez-Hernandez, 1979;Fages et al, 1988;Tansey et al, 1991). However, we found that ABHD6 and glutamine synthetase staining were mutually exclusive (Fig.…”
Section: Mgl Limits Duration Of Dse 1223mentioning
confidence: 98%
“…enzyme involved in the glutamate-glutamine cycle specific to astrocytes (Fages et al, 1988). Previous work has shown that GS is expressed in GFAP-expressing horizontal astrocytes within the SGL, but not in radial GFAP-expressing stem cells (Seri et al, 2004).…”
Section: Nestin-gfp Is Not Expressed In Reactive Astrocytes But Is Spmentioning
confidence: 98%